Differences in Implementation Outcomes of a Shared Decision-Making Program for Men with Prostate Cancer between an Academic Medical Center and County Health Care System. (February 2021) - Li, Kevin D.; Saigal, Christopher S.; Tandel, Megha D.; Kwan, Lorna; Inkelas, Moira; Alden, Dana L.; Frencher, Stanley K.; Gollapudi, Kiran; Blumberg, Jeremy; Nabhani, Jamal; Bergman, Jonathan
Background: Shared decision making (SDM) has long been advocated as the preferred way for physicians and men with prostate cancer to make treatment decisions. However, the implementation of formal SDM programs in routine care remains limited, and implementation outcomes for disadvantaged populations are especially poorly described. We describe the implementation outcomes between academic and county health care settings. Methods: We administered a decision aid (DA) for men with localized prostate cancer at an academic center and across a county health care system. Our implementation was guided by the Consolidated Framework for Implementation Research and the Reach, Effectiveness, Adoption, Implementation, and Maintenance framework. We assessed the effectiveness of the DA through a postappointment patient survey. Results: Sites differed by patient demographic/clinical characteristics. Reach (DA invitation rate) was similar and insensitive to implementation strategies at the academic center and county (66% v. 60%, P = 0.37). Fidelity (DA completion rate) was also similar at the academic center and county (77% v. 80%, P = 0.74). DA effectiveness was similar between sites, except for higher academic center ratings for net promoter for the doctor (77% v. 37%, P = 0.01) and the health care system (77% v. 35%, P = 0.006) and greater satisfaction with manner of care (medians 100 v. 87.5, P = 0.04). Implementation strategies (e.g., faxing of patients' records and meeting patients in the clinic to complete the DA) represented substantial practice changes at both sites. The completion rate increased following the onset of reminder calls at the academic center and the creation of a Spanish module at the county. Conclusions: Successful DA implementation efforts should focus on patient engagement and access. SDM may broadly benefit patients and health care systems regardless of patient demographic/clinical characteristics.